Peran Koneksi Politik dalam Melakukan Tax Avoidance - Moh. Ubaidillah (Politeknik Ganesha Medan, 2022)
This research aims to find out the effect of profit management, company size, profitability on tax avoidance with political connections as a moderation variable. The population of this study uses manufacturing companies registered with the IDX in 2017-2020 as many as 193 companies. This sampling technique uses purposive sampling that produces 36 companies. Data analysis techniques use regression analysis with the SPSS 24 tool. The results of this study show that profit management and profitability have a positive effect on tax avoidance. The size of the company has no effect on tax avoidance. Political connections are able to moderate the influence of profit management and profitability to tax avoidance. Political connections do not have the ability to moderate the influence of corporate size on tax avoidance.